Biocatalytic synthesis of chiral N-(2-hydroxyalkyl)-acrylamides - Monsalve, Leandro Nicolas; Rustoy, Eduardo Miguel; Baldessari, Alicia (Biocatalysis and Biotransformation)
The preparation of a series of novel chiral N-(2-hydroxylalkyl)-acrylamides through a lipase-catalyzed resolution of racemic alkanolamines is described. The absolute stereochemistry and enantiomeric excess of the products were determined by a modified Mosher's method. The method was validated for this particular case by the synthesis of an enantiomerically pure product. Moreover, the stereoselective behavior of the lipase in this reaction is discussed. Fil: Monsalve, Leandro Nicolas. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina Fil: Rustoy, Eduardo Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Orgánica; Argentina